2014
DOI: 10.1021/am5018072
|View full text |Cite
|
Sign up to set email alerts
|

PDMS-based Triboelectric and Transparent Nanogenerators with ZnO Nanorod Arrays

Abstract: Vertically-grown ZnO nanorod arrays (NRAs) on indium tin oxide (ITO)-coated polyethylene terephthalate (PET), as a top electrode of nanogenerators, were investigated for the antireflective property as well as an efficient contact surface in bare polydimethysiloxane (PDMS)-based triboelectric nanogenerators. Compared to conventional ITO-coated PET (i.e., ITO/PET), the ZnO NRAs considerably suppressed the reflectance from 20 to 9.7% at wavelengths of 300-1100 nm, creating a highly transparent top electrode, as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
125
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(133 citation statements)
references
References 25 publications
8
125
0
Order By: Relevance
“…It is evident that the average voltage and current (solid parts of peaks in each figure) gradually increase with the increase of frequency, while the maximum upper peak voltage remains almost same at around 20 V. The increase in average voltage and current is attributed to the increase in the average surface charge as the bending frequency is increased. This occurs due to the slower discharge rate of the device as compared to the input pulse rate, resulting in a continuous rise in the output voltage and current as frequency is increased [29,30]. At 30 Hz, the peak value of average voltage and current is 5.8 V and 3.2 µA (see Table 2), while the maximum upper peak value of voltage and current is 20 V and 6.5 µA.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that the average voltage and current (solid parts of peaks in each figure) gradually increase with the increase of frequency, while the maximum upper peak voltage remains almost same at around 20 V. The increase in average voltage and current is attributed to the increase in the average surface charge as the bending frequency is increased. This occurs due to the slower discharge rate of the device as compared to the input pulse rate, resulting in a continuous rise in the output voltage and current as frequency is increased [29,30]. At 30 Hz, the peak value of average voltage and current is 5.8 V and 3.2 µA (see Table 2), while the maximum upper peak value of voltage and current is 20 V and 6.5 µA.…”
Section: Resultsmentioning
confidence: 99%
“…The triboelectricity has recently been attracting a great deal of attention since it turned out to be a very promising concept in view of the energy harvesting. [18][19][20] In the energy harvesting device consisting of PDMS and ZnO, the repetitive pushing/separating operations generated positive/negative current signal. 18 PDMS was negatively charged relative to ZnO.…”
Section: -15mentioning
confidence: 99%
“…[18][19][20] In the energy harvesting device consisting of PDMS and ZnO, the repetitive pushing/separating operations generated positive/negative current signal. 18 PDMS was negatively charged relative to ZnO. Assuming ZnO and ZnS to be similar in terms of dielectric property, a certain amount of charge would be accumulated on the interface between the ZnS:Cu particle and the PDMS matrix during the elongation/retreat of the ZnS:Cu-PDMS composite.…”
Section: -15mentioning
confidence: 99%
“…In addition, transparent TENGs using indium tin oxide (ITO) or graphene as electrodes have been achieved, which enable applications that require high transparency such as touch screens [31][32][33][34][35] . Our previous work shows that using C 4 F 8 to treat uncured PDMS could deposit fluorocarbon polymer and a wrinkle structure in single step [18][19][20] , which had the advantage of significantly increasing the performance of the flexible TENG.…”
Section: Introductionmentioning
confidence: 99%
“…Although using a flat surface could provide the highest transparency, the performance of the TENGs will be weakened to some degree 38 . Notably, previous work reported that a PDMS surface with nanopattern sizes o 310 nm could result in high transmittances (above 85%) owing to an effective graded refractive index profile 32,33 . Using a structure of several hundred nanometers provides us with an effective way to realize highperformance and highly transparent TENGs.…”
Section: Introductionmentioning
confidence: 99%